Retroviral Vector Production. (17th April 2014) - Miller, A. Dusty
Abstract: In this unit, the basic protocol generates stable cell lines that produce retroviral vectors that carry selectable markers. Also included are an alternate protocol that applies when the retroviral vector does not carry a selectable marker, and another alternate protocol for rapidly generating retroviral vector preparations by transient transfection. A support protocol describes construction of the retroviral vectors. The methods for generating virus from retroviral vector plasmids rely on the use of packaging cells that synthesize all of the retroviral proteins but do not produce replication‐competent virus. Additional protocols detail plasmid transfection, virus titration, assay for replication‐competent virus, and histochemical staining to detect transfer of a vector encoding alkaline phosphatase. Curr. Protoc. Hum. Genet . 80:12.5.1‐12.5.22. © 2014 by John Wiley & Sons, Inc.